Important Coins from the Collection of Klaus Grigo - Wünsch, Julian (KOINON: The International Journal of Classical Numismatic Studies, 2023)
This article presents selected coins from the collection of Klaus Grigo from Bochum. Mr. Grigo’s enthusiasm for ancient numismatics was sparked when he obtained his first Roman coins, found during the drought of the Moselle in 1959. In 1976, he started collecting Greek coins until he first came into contact with pieces from Baktria at the Bochum Coin Exchange in 1988. Since then, he has compiled a collection of more than 550 eastern coins, ranging from the Achaemenids to the Indo-Parthians. After having acquired many rare and in part unpublished variants, Mr. Grigo decided to sell his coins in Gorny & Mosch’s Auction 297. Part 1, held on October 9, 2023. Following are a selection of previously unpublished rarities from the Grigo collection. For the other coins of the collection that couldn’t be included in this article, please refer to the auction catalogue.